PENGARUH TOTAL QUALITY MANAGEMENT DAN KINERJA KEBERLANJUTAN PELAYANAN DENGAN MEDIASI INOVASI LAYANAN - Abimatha, Daksa; Muhammad, Akmal Aziz; Martadisastra, Dedie S (JOURNAL OF BUSINESS STUDIES, 2024)
This research aims to analyze the influence of Total Quality Management (TQM) on sustainability performance by examining the mediating role of service innovation. With This research was conducted through hypothesis testing and data collection using non-probability sampling. This research was conducted quantitatively by distributing questionnaires, resulting in 218 employees. The five dimensions of TQM—leadership, people, process, strategy and policy, and partnership and resources—were identified as the main factors in supporting the sustainability performance of the organization. The data processing techniques used include validity tests, reliability tests, and descriptive statistics using SPSS 25 software.The research results show that TQM has a significant impact on sustainability performance and service innovation. However, service innovation does not show a significant direct effect on sustainability performance, nor does it mediate the relationship between TQM and sustainability performance. These findings indicate that although TQM practices can enhance service quality and innovation, the direct path to sustainability performance may involve factors beyond innovation.